Manipulating mentors' assessment decisions: Do underperforming student nurses use coercive strategies to influence mentors' practical assessment decisions?. (September 2016) - Hunt, Louise.A.; McGee, Paula; Gutteridge, Robin; Hughes, Malcolm
Abstract: There is growing evidence of a culture of expectation among nursing students in Universities which leads to narcissistic behaviour. Evidence is growing that some student nurses are disrespectful and rude towards their university lecturers. There has been little investigation into whether they exhibit similar behaviour towards their mentors during practical placements, particularly when they, the students, are not meeting the required standards for practice. This paper focuses on adding to the evidence around a unique finding – that student nurses can use coercive and manipulative behaviour to elicit a successful outcome to their practice learning assessment (as noted in Hunt et al. (2016, p 82)). Four types of coercive student behaviour were identified and classified as: ingratiators, diverters, disparagers and aggressors, each of which engendered varying degrees of fear and guilt in mentors. The effects of each type of behaviour are discussed and considered in the light of psychological contracts. Mechanisms to maintain effective working relationships between student nurses and mentors and bolster the robustness of the practical assessment process under such circumstances are discussed. Highlights: Student nurses are expected to behave in a professional way towards others. Many students behaved coercively and manipulatively when mentors told them their practice did not meet the pass criteria. Four coercive behaviour types emerged: ingratiators, diverters, disparagers, aggressors, causing fear and guilt in mentors. A four pronged approach is recommended to manage coercive and manipulative students and build mentor resilience.